To solve for \( x \) in the equation
\[ -12 + x = 48, \]
you can add 12 to both sides:
\[ x = 48 + 12. \]
So,
\[ x = 60. \]
Thus, the solution is
\[ \boxed{60}. \]
-12 + x =48
11 answers
To solve for \( x \) in the equation
\[ -12 + x = 48, \]
you can add 12 to both sides:
\[ x = 48 + 12. \]
So,
\[ x = 60. \]
Thus, the solution is
\[ \boxed{60}. \]
From the previous equation \(-12 + x = 48\), we solved for \( x \) and found that:
\[ x = 60. \]
Therefore, the value of \( x \) is
\[ \boxed{60}. \]
The solution \( x = 60 \) is a positive number.
To solve for \( x \) in the equation
\[ x - 25 = 5, \]
you can add 25 to both sides:
\[ x = 5 + 25. \]
So,
\[ x = 30. \]
Thus, the solution is
\[ \boxed{30}. \]
Sure! Let's solve the equation step by step in a more conversational manner.
You have the equation:
\[ x - 25 = 5. \]
To find \( x \), you can add 25 to both sides of the equation. This gives you:
\[ x = 5 + 25. \]
Calculating that:
\[ x = 30. \]
Now, regarding whether 30 is negative or positive: 30 is a positive number.
So, the final answer is:
x = 30 (positive).
To solve the equation
\[ 4x = -24, \]
you need to isolate \( x \). You can do this by dividing both sides of the equation by 4:
\[ x = \frac{-24}{4}. \]
Calculating that gives:
\[ x = -6. \]
So, the solution is
\[ \boxed{-6}. \]
And since \(-6\) is less than 0, it is a negative number.